COVID-19-associated coagulopathy in children and adolescents - M. V. Gomellya; A. V. Tatarinova; T. S. Krupskaya; L. V. Rychkova (Acta Biomedica Scientifica, 2021)
The pandemic of the new coronavirus infection COVID-19 in 2020 has become the main health problem across the globe. A special characteristic of the SARSCoV-2 virus is tropism to the vascular endothelium with the  development of endotheliitis, which entails a number of typical disorders of the blood coagulation system: coagulopathy with increased thrombin generation, D-dimer, decreased fibrinolysis and prolonged prothrombin time. The coagulation disorder in COVID-19 is called thromboinflammation. Hyperinflammation, increased blood levels of von Willebrand factor, coagulation factor VIII, neutrophil extracellular traps, platelet activation, microvesicles play a significant role in the pathogenesis of hypercoagulation in COVID-19. To date, it is known that cases of COVID-19 in children and adolescents constitute a small part of the total number of patients with diagnosed COVID-19, and disorders of the blood coagulation system are similar to those in adults. The degree of hypercoagulable syndrome and the risk of thrombosis depend on the severity of COVID-19. And for children they are most expressed with the development of a hyperinflammatory immune response, called multisystem inflammatory syndrome. At the same time, clinical studies of the pathogenesis of COVID-19 in adults and children and the search for optimal methods of therapy for thrombus inflammation, which underlies the pathogenesis of COVID-19, continue.